Happy Heartwood Day - Kirk, David, 1955- (New York, N.Y. : Grosset & Dunlap/Callaway, 2005)
On Heartwood Day in Sunny Patch, all the bugs have a big party and give and receive gifts, except for Dragon, who needs to learn how to share.
"This book is based on the TV episode $1 (BHappy Heartwood Day,$1 (Bwritten by Alice Prodanou, from the animated TV series Miss Spider$1 (Bs Sunny Patch friends."s
Keywords: Insects -- Juvenile fiction; Holidays -- Juvenile fiction; Parties -- Juvenile fiction; Sharing -- Juvenile fiction; Insects -- Fiction; Holidays -- Fiction; Parties -- Fiction; Sharing -- Fiction; Radio and television novels